The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1785/0120180049
|View full text |Cite
|
Sign up to set email alerts
|

Do Directionality Effects Influence Expected Damage? A Case Study of the 2017 Central Mexico Earthquake

Abstract: We analyze the case of a building that collapsed in a multifamily complex of Tlalpan borough in Mexico City during the 19 September 2017 Central Mexico earthquake. Despite having similar materials and similar structural and geometric properties, this was the only building that collapsed in the complex. A structural analysis of the building and a study of the soils' predominant periods indicated that resonance effects, if any, would not be significant. However, phenomena related to the anomalous performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 28 publications
4
34
0
6
Order By: Relevance
“…It has been demonstrated that the structural response strongly varies depending on the orientation of the structure with respect to the seismic action. For instance, Vargas-Alzate et al [2018] and Pinzón et al [2018a] demonstrated how buildings with very similar structural system and dimensions, located very close to each other, had different damage states depending on their orientation respect to the earthquake source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the structural response strongly varies depending on the orientation of the structure with respect to the seismic action. For instance, Vargas-Alzate et al [2018] and Pinzón et al [2018a] demonstrated how buildings with very similar structural system and dimensions, located very close to each other, had different damage states depending on their orientation respect to the earthquake source.…”
Section: Discussionmentioning
confidence: 99%
“…Notice that, the predominant acceleration acting on a structure will also depend on its azimuthal orientation. This effect has been widely studied focusing on the expected performance and damage in structures and on the seismic hazard [Lagaros, 2010;Mackie et al, 2011;Nguyen and Kim, 2013;Torbol and Shinozuka, 2014;Bradley and Baker, 2015;Fontara et al, 2015;Vargas-Alzate et al, 2018;Pinzón et al, 2018a].…”
Section: Introductionmentioning
confidence: 99%
“…RotD100 is the spectrum that represents the maximum (100th percentile) values of response spectra of the two as-recorded horizontal components rotated onto all non-redundant azimuths [13]. This is due to the directionality effect of strong motion recordings, which is now considered in the GMPEs [12,14,15] and in the variability of the performance of structures due to the angle of incidence of the seismic action [16][17][18][19].…”
Section: Impact On the Smart Home Networkmentioning
confidence: 99%
“…Buildings in the San Fernando neighborhood suffered various damage grades. Significant differences among damaged nearby buildings have been attributed to directionality effects of the strong ground motions [2,3].…”
Section: Introductionmentioning
confidence: 99%